1991
DOI: 10.1017/s0094837300010459
|View full text |Cite
|
Sign up to set email alerts
|

Bias of the paleobotanical record as a consequence of variations in the chemical composition of higher vascular plant cuticles

Abstract: The impact of the variations in the chemical composition of higher vascular plant cuticles on their fossil record is usually not considered in paleobotanical and, more particularly, taphonomic studies. Here we address the subject with reference to the chemical characterization of insoluble cuticular matrices of a large variety of recent and fossil cuticles. The cuticles were analyzed using Curie-point pyrolysis-gas chromatographic techniques. Cuticular matrices of extant higher plants consist either of the bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
0
3

Year Published

1996
1996
2013
2013

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(78 citation statements)
references
References 26 publications
2
73
0
3
Order By: Relevance
“…The actual chemical nature of the intermolecular linkages involved in the binding of pCA and FA to the leaf waxes are still unknown, though the fact that both compounds are only released by saponification suggests that either the carboxylic acid or the hydroxyl group is involved. Since it was shown that especially the former group is involved in linkages to carbohydrates (Carnachan and Harris 2000) and fatty alcohols (Mahmood et al 2003) this suggests that most likely pCA and FA are linked to the hydroxyl groups of cutin (the solvent insoluble biopolymer in plant cuticles (Tegelaar et al 1991))-like monomers (see also; Mo¨sle et al 1997;Mo¨sle et al 1998;van Bergen et al 2004). Other examples of esterified pCA can be found in flavonol glycosides such as present in the leaves of Planchonia grandis (Crublet et al 2003).…”
Section: Functions Of Pca and Fa In Plantsmentioning
confidence: 99%
“…The actual chemical nature of the intermolecular linkages involved in the binding of pCA and FA to the leaf waxes are still unknown, though the fact that both compounds are only released by saponification suggests that either the carboxylic acid or the hydroxyl group is involved. Since it was shown that especially the former group is involved in linkages to carbohydrates (Carnachan and Harris 2000) and fatty alcohols (Mahmood et al 2003) this suggests that most likely pCA and FA are linked to the hydroxyl groups of cutin (the solvent insoluble biopolymer in plant cuticles (Tegelaar et al 1991))-like monomers (see also; Mo¨sle et al 1997;Mo¨sle et al 1998;van Bergen et al 2004). Other examples of esterified pCA can be found in flavonol glycosides such as present in the leaves of Planchonia grandis (Crublet et al 2003).…”
Section: Functions Of Pca and Fa In Plantsmentioning
confidence: 99%
“…Cutin and cutan behave dierently when subject to the biochemical degradation process that occur during diagenesis, with cutan being found to be the durable constituent in all fossilised plant cuticles studied (Tegelaar et al 1991). In contrast, cutin, the common biopolymer constituting the cuticular matrix of the cuticular membrane of higher plants, is much less stable due to the presence of hydrolyzable intermolecular linkages.…”
Section: Agave Americana Clivia Miniatamentioning
confidence: 99%
“…It has also been suggested (Nip et al 1986a, b) that cutan may be ubiquitous in plants since it has been reported to be a constituent in fossilised plant cuticles, terrestrial sediments and coals covering a large part of the geological past. Although the cuticles of some species appear to completely lack cutans, notably those of tomato fruits and Citrus and Erica leaves (Tegelaar et al 1991), cutan may be the principal biopolymer in some others, notably in Beta vulgaris, and the mixed cutin/cutan type of cuticular membrane may turn out to be very widespread. The two biopolymers may occur in any ratio (Tegelaar 1990), and dier in their relative abundance at dierent stages of cuticle development.…”
Section: Introductionmentioning
confidence: 99%
“…As is the problem with sporopollenin (see above) the genesis of an aliphatic geopolymer replacing the cutin in the original cuticles has to be assumed (cf. Tegelaar et al 1991;Collinson et al 1998). In this particular case the most likely candidates to be transferred diagenetically into an aliphatic polymer are cutin (cf.…”
Section: Cutin and Cutanmentioning
confidence: 99%